Re-test reliability and internal consistency of EEG alpha-band oscillations in older adults with chronic knee pain. Issue 11 (November 2020) - Rocha, Harold A.; Marks, John; Woods, Adam J.; Staud, Roland; Sibille, Kimberly; Keil, Andreas
Highlights: We establish EEG alpha power reliability and consistency in chronic knee pain. Alpha power in chronic knee pain is reliable and consistent across recordings, sites. Recommendations are provided for quantifying alpha-related measures in pain research. Abstract: Objective: Chronic pain studies investigating the ability to detect sensory processing differences related to thalamic gating using electroencephalographic (EEG) alpha have yielded conflicting results. Alpha's basic psychometric properties in pain populations requires further study. The present study reports on the test–retest reliability and internal consistency of EEG alpha power in older adults with chronic knee pain. Methods: Repeated EEG alpha power measurements were taken of older adults (N = 31) with chronic knee pain across two sessions separated by a ten-day period associated with a pilot clinical trial study. Recordings included resting periods (eyes open and eyes closed) as well as periods involving a pain management activity. Results: Most single alpha-power measures and all within-participant averages of alpha obtained within a session showed high internal consistency (Cronbach's α > 0.7) and satisfactory-to-excellent re-test reliability (Pearson's rs > 0.6) of both alpha power and alpha blocking (eyes closed minus eyes open) across repeated conditions. Conclusions: EEG alpha power seems mostly reliable and consistent, particularly when participants' eyes are closed, after a period of habituation, and when alpha measures are averaged as within-participant estimates. Significance: This analysis suggests that within-subject averages of EEG alpha are the most reliable for developing indices of chronic knee pain.